Single arterial access for Ecpella and jugular venous cannulation provides full mobility on a status 1 heart transplant recipient. (23rd February 2022) - Bitargil, Macit; Pham, Si; Haddad, Osama; Sareyyupoglu, Basar
Abstract: Concomitant treatment with veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) and Impella may improve outcomes in patients with cardiogenic shock compared with VA‐ECMO alone. Here, we explain a new method to introduce Impella and ECMO through the same arterial access site and jugular venous cannulation to accomplish a mobile patient concept.